1994
DOI: 10.1007/bf00201587
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of the human electroencephalogram (EEG) and event-related brain potentials (ERPs): a review

Abstract: Twin and family studies of normal variation in the human electroencephalogram (EEG) and event related potentials (ERPs) are reviewed. Most of these studies are characterized by small sample sizes. However, by summarizing these studies in one paper, we may be able to gain some insight into the genetic influences on individual differences in central nervous system functioning that may mediate genetically determined differences in behavior. It is clear that most EEG parameters are to a large extent genetically de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
100
3
3

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 166 publications
(113 citation statements)
references
References 72 publications
(92 reference statements)
3
100
3
3
Order By: Relevance
“…Speed of target and nontarget processing appeared to be influenced strongly by genetic effects. This contrasts with the results of two other large twin studies on P3 that did not find evidence for heritability of P3 latency in adults or adolescents (O'Connor et al, 1994;van Beijsterveldt, 1996). A reason for this discrepancy is provided by the study of Katsanis et al (1997).…”
Section: Discussioncontrasting
confidence: 91%
See 4 more Smart Citations
“…Speed of target and nontarget processing appeared to be influenced strongly by genetic effects. This contrasts with the results of two other large twin studies on P3 that did not find evidence for heritability of P3 latency in adults or adolescents (O'Connor et al, 1994;van Beijsterveldt, 1996). A reason for this discrepancy is provided by the study of Katsanis et al (1997).…”
Section: Discussioncontrasting
confidence: 91%
“…No data were reported on nontarget amplitudes. Using the same visual oddball as this study, van Beijsterveldt (1996) found heritability to range from 42% to 60% in a large group of adolescent twins. In agreement with our finding in children, the individual variation in P3 amplitude to nontargets was mainly genetic in the adolescents and, there too, heritability of nontarget amplitude was higher than that of the targets.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations